Construção de uma biblioteca de anticorpos recombinantes (FAB) anti-carcinoma mamário e obtenção de fragmentos ligantes de antígenos tumorais por phage display - Araújo, Thaise Gonçalves de (2009)
Breast carcinoma (BC) is currently regarded as a complex and heterogeneous disease presenting abnormalities in several molecular pathways. Although BC is the leading female cancer in incidence and the second one in mortality worldwide, the prognostic and predictive factors known are incapable to predict the outcome of all patients as well as to avoid unnecessary treatment. Applicability of Phage Display technology allows the construction of antibody combinatorial libraries identifying human monoclonal antibodies to clinical and therapeutic practice. In this work was constructed a recombinant Fab library which aimed recognized tumor antigens in patients with breast cancer. Transcripts from twenty patients with diagnosed invasive ductal carcinoma were used to construct a library with 1,7x106 different clones, which was selected against breast tissues. ELISA assays demonstrated reactivity of 22 clones, of which was selected the one with the biggest difference between the study groups. Imunohistochemistry experiments confirmed the specificity of FabC-4 clone to tumor antigens. This work provided significant biotechnological results with a specific Fab recombinant library, which indicated its great potential in selecting antibodies for breast carcinoma, opening new possibilities in diagnostic and therapeutics areas.